Analisis konsistensi penggunaan lahan terhadap peta RTRW provinsi Riau di desa Beringin Jaya - Muammar, Ahmad Allaam; Amrullah, M. Nur Kamila (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2023)
The Regional Spatial Plan (RTRW) is the basis on which the government carries out regional development. To ensure that development is carried out according to regulations, it is important to ensure compatibility between land use and the RTRW Map. Land problems arose in Beringin Jaya Village, Riau Province, due to the expansion of plantation land that penetrated into forest areas. This study aims to evaluate the extent to which the RTRW Map issued by the Provincial Government of Riau corresponds to the actual field conditions. The results showed that the level of suitability between land use and the RTRW Map was 67.78% suitable, 30.42% not suitable, and 1.48% supported. Furthermore, a suitability analysis between land parcels that have SHAT and the RTRW is carried out through overlay using parcel data downloaded with the RTRW Map. From the results of the Land Use Map overlay, it was revealed that 29% of the total area was determined according to the spatial plan, while 49% of the 45 sampled plots of land were located outside the forest area. . Thus, the local regional government needs to work together with relevant agencies in formulating appropriate, effective and efficient policies so that problems related to spatial planning can be resolved and then the Governor needs to submit a request to the Ministry of Environment and Forestry to form an Integrated Team. Rencana Tata Ruang Wilayah (RTRW) merupakan dasar bagi pemerintah dalam melaksanakan pembangunan daerah. Untuk memastikan bahwa pembangunan dilakukan sesuai dengan peraturan, penting untuk memastikan kesesuaian antara penggunaan lahan dengan Peta RTRW. Permasalahan pertanahan muncul di Desa Beringin Jaya, Provinsi Riau, karena perluasan lahan perkebunan yang merambah ke kawasan hutan. Penelitian ini bertujuan untuk mengevaluasi sejauh mana Peta RTRW yang diterbitkan oleh Pemerintah Provinsi Riau sesuai dengan kondisi lapangan yang sebenarnya. Hasil penelitian menunjukkan tingkat kesesuaian antara penggunaan lahan dan Peta RTRW sebesar 67,78% sesuai, 30,42% tidak sesuai, dan 1,48% mendukung. Selanjutnya, analisis kesesuaian antara bidang tanah yang memiliki SHAT dengan RTRW dilakukan melalui overlay menggunakan data persil yang diunduh dengan Peta RTRW. Dari hasil overlay Peta Penggunaan Lahan, terungkap bahwa 29% dari total luas wilayah yang ditetapkan sesuai dengan tata ruang, sementara 49% dari 45 sampel bidang tanah berada di luar kawasan hutan. Dengan demikian, pemerintah daerah setempat perlu bekerja sama dengan instansi terkait dalam merumuskan kebijakan yang sesuai, efektif, dan efisien sehingga permasalahan terkait penataan ruang dapat terselesaikan dan kemudian Gubernur perlu mengajukan permohonan kepada Kementerian LHK untuk dibentuk Tim Terpadu.